Scattering methods and their application in colloid and interface science - Glatter, O. (Elsevier, 2018)
Scattering Methods and their Application in Colloid and Interface Science offers an overview of small-angle X-ray and neutron scattering techniques (SAXS & SANS), as well as static and dynamic light scattering (SLS & DLS). These scattering techniques are central to the study of soft matter, such as colloidal dispersions and surfactant self-assembly. The theoretical concepts are followed by an overview of instrumentation and a detailed description of the evaluation techniques in the first part of the book. In the second part, several typical application examples are used to show the strength and limitations of these techniques.